2022
DOI: 10.1001/jamanetworkopen.2022.27443
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Surgical Response and Associated Volume Trends Throughout the COVID-19 Pandemic and Postvaccination Recovery Period

Abstract: Key Points Question How did surgical volumes change with respect to subspecialty and patient acuity during the COVID-19 pandemic, and did they recover after the peak and vaccine release periods? Findings In this cohort study, a retrospective analysis of 129 956 records of weekly surgical procedures from January 6, 2019, to December 31, 2021, revealed that the overall volume did not fully recover to pre–COVID-19 levels well into 2021. Recovery rates were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 22 publications
4
16
0
4
Order By: Relevance
“…Although the impact was largest during the COVID‐19 peak in mid‐2020, the provision of health care has not fully rebounded. For example, surgical oncology procedures at Massachusetts General Hospital were 72% of 2019 levels during the last one half of 2020 and were only 84% in 2021, the lowest recovery of any surgical specialty 1 . Delays in diagnosis and treatment may lead to an uptick in advanced‐stage disease and mortality 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the impact was largest during the COVID‐19 peak in mid‐2020, the provision of health care has not fully rebounded. For example, surgical oncology procedures at Massachusetts General Hospital were 72% of 2019 levels during the last one half of 2020 and were only 84% in 2021, the lowest recovery of any surgical specialty 1 . Delays in diagnosis and treatment may lead to an uptick in advanced‐stage disease and mortality 2 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, surgical oncology procedures at Massachusetts General Hospital were 72% of 2019 levels during the last one half of 2020 and were only 84% in 2021, the lowest recovery of any surgical specialty. 1 Delays in diagnosis and treatment may lead to an uptick in advanced-stage disease and mortality. 2 These and other secondary consequences of the pandemic will occur gradually over time and will require many years to quantify at the population level because of the 2-year to 3-year lag in population-based cancer incidence and mortality data.…”
Section: Introductionmentioning
confidence: 99%
“…This could reflect a general stabilization in blood use in the broader healthcare system, with a continued trend toward less‐invasive surgeries but a nadir in the effect of increased adoption of patient blood management programs in non‐surgical clinical settings. Furthermore, the slightly more pronounced decrease in transfusions in surgery settings in 2021 compared to prior years could also reflect a continued impact the COVID‐19 pandemic had on surgery cancelations, as the surgical volume had not fully rebounded to pre‐pandemic levels by the beginning of 2021 18 . Additionally, unlike NBCUS results from 2017 and 2019, in 2021 there was less variability seen in differences in RBC use by hospital size.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective time-series analysis of all surgical procedures conducted at a similarly sized tertiary care center in America found that urologic surgeries have only returned to 85% of pre-pandemic levels. 19 Deferral of surgical treatment is associated with significant risks ranging from deterioration in mental health and quality of life, to disease progression and increased rates of mortality. 20 Addressing backlogs is therefore crucial for minimizing patient morbidity and improving health outcomes.…”
Section: Cuaj -Original Researchmentioning
confidence: 99%